Trypanosoma evansi: Effects of zinc and copper in experimentally infected rats - Dalla Rosa L. (2012)
The aim of this study was to evaluate the effects of a treatment using injectable zinc and copper in rats infected with Trypanosoma evansi. 48 rats were divided into eight groups of six animals each. Group A was composed of uninfected animals. Animals from groups B-H were inoculated at the 5th day of experiment with 1.2×10 6 trypanosomes. Group B was used as a positive control. The infected groups received prophylactic (C, D and E) and therapeutic (F, G and H) treatments with the zinc and copper, both at a dose of 5mgkg -1. The effectiveness of treatment was confirmed by negative blood smears and Polymerase Chain Reaction (PCR) at the end of study. All treated animals had their prepatent period and survival prolonged when compared with control group (group B). Treatment efficacy was 17% (C: zinc), 33% (D: copper), 50% (E: zinc+copper), 0% (F: zinc), 50% (G: copper) and 50% (H: zinc+copper). Thus, we can conclude that treatment with zinc and copper are capable of controlling and/or curing T. evansi infection in rats, delaying the parasitemia and prolonging their survival. © 2012 Elsevier Inc.